Paraguay : Defining a Strategy for Social Protection Policy - World Bank (Washington, DC, 2013)
Despite the pervasive high incidence of poverty, Paraguay has not responded adequately to the need to develop a policy, aimed at providing effective protection to the population. In recent decades the social protection policies in Paraguay were not able to reduce the exposure to, and the consequences of social risks, due to flawed diagnosis, inappropriate program design, poor implementation, and budgetary restrictions. Nonetheless, the Government has identified some of these problems in recent years, and attempted to formulate reform proposals, but political and institutional obstacles prevented their implementation. Even though the Secretary for Social Action has developed the National Strategy for the Reduction of Poverty and Inequity, the institutional reforms and the protection programs proposed in it, have not been implemented. Likewise, both from the Executive Branch, and from parliamentary sectors, there have been attempts to reform the pension system, but no minimal consensus was reached, to enable discussion, and approval in Congress. Social protection policies and programs in Paraguay result from an approach to the problem, characterized by the absence of an integral strategic vision. The sector evolved as the accumulation of partial attempts to promote social protection actions, strongly influenced by sectoral interests, but it was rarely developed in an integrated manner, or based on a rigorous analysis of the real needs of the population. The report suggests that a sound proposal for restructuring the sector, requires the explicit formulation of a conceptual framework, in order to identify the priorities in a rigorous manner, and establish consistent methodologies for the selection, and execution of actions, developing an integral vision for the social protection policy in the country. In the context of this report, the interest is focused on a particular type of risk, which appears as central among the population's multiple problems: the insufficiency of monetary resources, expressed through poverty. In reference to that goal, we consider the two main components of the social protection policy: social assistance and pension systems. With respect to social assistance, the focus is directed to programs, and actions aimed at alleviating poverty of the population in general. With respect to pension systems, interest is concentrated on the actions of the State, to provide economic security for the elderly, who have already retired from the labor market. This report considers how Paraguay's social protection mechanisms work for individuals that have fallen into poverty, and lack resources and/or skills to overcome it. Therefore, social assistance policies are considered, while those related to general economic, and social development are not specifically contemplated. An effective social protection model in Paraguay must correctly identify social risks, and promote public actions that should not overlap, or limit individual, family, or community-based actions, but rather complement them.